A Study on English and Vietnamese Idioms of Comparison - Ngô Đình Diệu Tâm (2005)
Idioms in general and idioms of comparison in particular are of culture - specific nature that is governed by a diversity of natural and social factors whose influence varies from culture to culture. In this study, both linguistic and cultural aspects of idioms in English and Vietnamese language, in which the grammatical structure and semantic mechanism were discussed as the essential foundation for the following investigation into the cultural features. Also, the question of cultural governing factors was taken up. Data were collected from various dictionaries and collection books, then surveyed, classified, and constituently analysed to get a thorough study and provide an insightful view of idioms of comparison in English and Vietnamese. From the analysis of data, conclusions were drawn, findings were presented to test the validity of the initial hypotheses; some practical solutions were also suggested with the hope of partially helping to avoid interferences in language and culture as well.